Label-free aptasensor for the detection of cardiac biomarker myoglobin based on gold nanoparticles decorated boron nitride nanosheets - Adeel, Muhammad; Rahman, Md. Mahbubur; Lee, Jae-Joon (Biosensors & bioelectronics, 2019)
A novel electrochemical aptasensor based on gold nanoparticles decorated on boron nitride nanosheets (AuNPs/BNNSs) for the sensitive and selective detection of myoglobin (Mb) is reported. BNNSs were chemically synthesized by a low-cost and simple hydrothermal method. They were deposited onto the fluorine-doped tin oxide (FTO) electrode by a spin-coating method. Subsequently, AuNPs were chemically deposited onto the BNNS/FTO electrode by a seed-mediated chemical reduction method, with an average particle size of approximately 10 nm. The AuNPs/BNNSs/FTO electrode was used as a transducer to immobilize a thiol-functionalized DNA aptamer (Apt) via the covalent interaction of Au–S for the specific binding of Mb. [Fe(CN)6]3-/4- was used as a redox probe to monitor the oxidation current variation upon the binding of Mb with varying concentrations onto the sensor surface. The Apt/AuNPs/BNNSs/FTO sensor shows a high signal response for Mb with a detection limit of 34.6 ng/mL and a dynamic response range of 0.1–100 µg/mL. It is a promising candidate for point-of-care diagnosis in real samples. This strategy could make possible the application of other 2D materials with wide bandgaps for the development of biosensors. •AuNP/BNNS-modified FTO electrode is prepared for the aptamer-based detection of Mb.•AuNP/BNNS/FTO is used as a transducer to immobilize thiol-functionalized aptamer.•The immobilized aptamers allow the specific binding of target Mb biomarkers.•Variation of the oxidation signals of [Fe(CN)6]3-/4- enables the detection of Mb.•The aptasensor showed high performance for the sensitive detection of Mb.